The Effectiveness of Teaching Elementary School Students to Solve Logical Problems - Ismatullayevich, Boboyorov Davron (International Journal of Formal Education, 2025)
This article provides a scientific and theoretical analysis of modern pedagogical approaches to teaching primary school students to solve logical problems. The importance of didactic games, constructive methods, STEAM and modular education elements in the formation of logical thinking is shown. A comparative analysis is conducted based on practical experience in the education systems of Uzbekistan and foreign countries, and existing problems are analyzed based on the results of international assessment programs (TIMSS, PISA). The prospects for developing logical problem-solving skills in education are substantiated through the forecasts and proposals put forward by the author. The article contains useful scientific and practical recommendations for educators, methodologists and education policymakers working in the field of primary education.